Urinary cadmium concentration is associated with the severity and clinical outcomes of COVID-19: a bicenter observational cohort study - Li-Chung Chiu; Chung-Shu Lee; Ping-Chih Hsu; Hsin-Hsien Li; Tien-Ming Chan; Ching-Chung Hsiao; Scott Chih-Hsi Kuo; How-Wen Ko; Shu-Min Lin; Chun-Hua Wang; Horng-Chyuan Lin; Pao-Hsien Chu; et al. (BMC, 2024)
Abstract Background Cadmium and nickel exposure can cause oxidative stress, induce inflammation, inhibit immune function, and therefore has significant impacts on the pathogenesis and severity of many diseases. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can also provoke oxidative stress and the dysregulation of inflammatory and immune responses. This study aimed to assess the potential associations of cadmium and nickel exposure with the severity and clinical outcomes of patients with coronavirus disease 2019 (COVID-19). Methods We performed a retrospective, observational, bicenter cohort analysis of patients with SARS-CoV-2 infection in Taiwan between June 2022 and July 2023. Cadmium and nickel concentrations in blood and urine were measured within 3 days of the diagnosis of acute SARS-CoV-2 infection, and the severity and clinical outcomes of patients with COVID-19 were analyzed. Results A total of 574 patients were analyzed and divided into a severe COVID-19 group (hospitalized patients) (n = 252; 43.9%), and non-severe COVID-19 group (n = 322; 56.1%). The overall in-hospital mortality rate was 11.8% (n = 68). The severe COVID-19 patients were older, had significantly more comorbidities, and significantly higher neutrophil/lymphocyte ratio, C-reactive protein, and interleukin-6 than the non-severe COVID-19 patients (all p < 0.05). Blood and urine cadmium and urine nickel concentrations were significantly higher in the severe COVID-19 patients than in the non-severe COVID-19 patients. Among the severe COVID-19 patients, those in higher urine cadmium/creatinine quartiles had a significantly higher risk of organ failure (i.e., higher APACHE II and SOFA scores), higher neutrophil/lymphocyte ratio, lower PaO2/FiO2 requiring higher invasive mechanical ventilation support, higher risk of acute respiratory distress syndrome, and higher 60-, 90-day, and all-cause hospital mortality (all p < 0.05). Multivariable logistic regression models revealed that urine cadmium/creatinine was independently associated with severe COVID-19 (adjusted OR 1.643 [95% CI 1.060-2.547], p = 0.026), and that a urine cadmium/creatinine value > 2.05 μg/g had the highest predictive value (adjusted OR 5.349, [95% CI 1.118-25.580], p = 0.036). Conclusions Urine cadmium concentration in the early course of COVID-19 could predict the severity and clinical outcomes of patients and was independently associated with the risk of severe COVID-19.